Nutritional Analysis of Locally Preferred Fodder Trees of Middle Hills of Nepal: A Case Study from Hemja VDC, Kaski District - Dhungana, Sunita; Tripathee, Hari P; Puri, Lila; Timilsina, Yajna P; Devkota, Krishna P (Nepal Journal of Science and Technology, 2013)
The study on nutritional value of locally preferred fodder trees in the farmland of middle hills of Nepal was conducted in Hemja VDC of Kaski district. Primary information on distribution and frequency of fodder trees was obtained through key informants survey, group discussion and observation of the study area. The preference ranking of ten most abundant fodder trees was done on the basis of palatability, propagation easiness, growth rate and competition with agricultural crops. The nutritional value of fodder species was analyzed and compared with the farmers’ preference ranking to examine association among them. The analysis correspond farmers’ preference of fodder tree species to their nutritional values. The study revealed that Ficus subinisa was the dominant fodder tree however, the Artocarpus lakoocha was highly preferred trees for its palatability and nourishing values. Nutritional analysis of ten preferred fodder species with respect to moisture, ash, crude protein, crude fat, crude fiber and carbohydrate was carried out. The crude protein varied from 15-29%, in which, A. lakoocha to contained the highest amount of crude protein. Similarly, F. lacor contained highest crude fiber (42.07%), and Machilus odoratissima yielded highest amount of carbohydrate (21.92%). Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 39-44 DOI: http://dx.doi.org/10.3126/njst.v13i2.7712